MENINGKATKAN KESEJAHTERAAN KEHIDUPAN PARA BURUH DI ERA GLOBALISASI YANG DIHADAPI BANGSA INDONESIA - Firmansyah, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2018)
The era of globalization facing the present for workers in the country of Indonesia at the moment is very concerned about its welfare therefore policyholders should think about how to get it out, workers have to execute their skills as professional workers who can compete with other countries and whether to increase human resources to get the workers recognized in other countries to compete. The purpose of this research is to improve the welfare of the workers in Indonesia. The method used is descriptive analysis of literature analysis. It can be concluded that the welfare of workers can improve the performance and welfare for the workers themselves to meet the needs of the family.